Firm R&D, Innovation, and Productivity in German Industry - Van Anh Vuong; Bettina Peters; Mark J. Roberts; Helmut Fryges (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper investigates empirically rm investment behavior in research and development (R&D). Firms make investments in R&D in order to produce innovations. These innovations in turn improve the rm s future productivity level, pro tability and incentives to invest in R&D. Using German rm-level data from the manufacturing sector, we estimate a dynamic, structural model of the rm s choice to invest in R&D and quantify the bene t and cost of engaging in R&D. We nd that among rms that engage in R&D, process and product innovations create a signi cant improvement in their productivity. The cost for performing R&D differs across rms based on their size and R&D history. We compute the bene ts of R&D investment to the rm and nd that by taking the dynamic nature of the investment into account the real return to R&D is several times higher than the one time gain in rm productivity.
Keywords: L60; O31; O32; 330